Pendampingan Mengintegrasikan ShopeePay sebagai Metode Pembayaran Untuk Meningkatkan Efisiensi Transaksi Pada Starra Kitchen - Zahro’, Afi Faridatas; Rahmawati, Afifah Suci; Wulandari, Afrilia; Akbar, Ahmad Riszki; Al-Akhsan, Ahmad Ghaffar; Mahfudhotin, Mahfudhotin; Fikriyah, Ashfa; Efendi, Rofik (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2024)
The use of digital payment methods has become a necessity for MSMEs in increasing operational efficiency and competitiveness, including Starra Kitchen, which is trying to follow this trend. This community service activity aims to assist Starra Kitchen in integrating ShopeePay as a digital payment method. The implementation of the activity involves a service learning approach involving a team of lecturers and students. The stages include identifying needs, training, technical implementation, and evaluation. The training includes account creation, ShopeePay application integration, and simulation of its use. This activity is carried out in a participatory manner through discussions and direct assistance. The results of the activity show that Starra Kitchen has succeeded in integrating ShopeePay as a payment method, which is expected to increase transaction efficiency, reduce recording errors, and expand customer access. The success of this activity is the first step in Starra Kitchen's digital transformation, as well as encouraging MSMEs to utilize financial technology to improve the sustainability and competitiveness of their businesses.